The impact of animation program on Arabic learning vocabulary recall among primary school pupels: a case study at a selected Islamic Primary School, Gombak - Ahmed Mohamed, Ismaiel Hassanein; Mokhtar, Mahani (Persatuan Bekas Mahasiswa Islam Timur Tengah, 2020)
An effective way of learning language vocabulary requires various types of teaching and strategies . The animated cartoon or films can accelerate enjoyment and interest for student to expand their Arabic vocabulary recall. This research aimed to investigate the effectiveness of the usage of animation program in Arabic language learning on vocabulary recall and basic verbal skills among the first year pupels in a selected Islamic Primary School in the district of Gombak, Selangor. To achieve the objectives of the study, the researchers adopted the experimental approach via control and experimental groups. Two classes of similar academic level were selected comprising 40 students, with 20 students in each class. In the control group, picture animations were used, while the control group involved normal and traditional teaching strategies. The study was carried out during the second term of the school year 2016. The vocabulary recall tests consisted of twenty (20) words whilst the verbal skills test consisted of six (6) sentences. Descriptive analyses was done on the data. The results showed that level of effectiveness of the usage of animation program in achieving the objectives of this study. In the light of those findings, the study urged the usage of animation programs in Arabic language learning for primary school students to enhance the learning of vocabulary and basic verbal skills, not as an alternative but as an additional technique. It was also suggested that further researches be done on how to maximise the usage of animation programs in Arabic Language Learning in primary school and what kind of animation programs would be most effective in Arabic language learning amongst primary school students.